Generation change in agriculture: A systematic review of the literature - Áron József Borda; Balázs Sárvári; Jeremiás Máté Balogh (Economies, 2023)
Today, the replacement of the ageing agricultural population is a global challenge in many food-producing countries. This article aims to provide an overview of generational change in agriculture based on the literature in international economics published in recent years, using a systematic review of the scientific literature. Research has identified several factors as barriers to agricultural generational change. Young people are less motivated to take over family farms. Farming does not offer them sufficient income, and the working conditions are not ideal. Access to land is severely limited worldwide, and the market bargaining power of the younger generation is low. Administrative burdens are also a barrier to the generational renewal of farms. The effects of climate change also have the potential to discourage next-generation farmers. Financial support for generational change in agriculture could be one solution to all these problems. Furthermore, generational change can be enhanced by the modernization of farms, providing farmers with access to land, and making a positive difference to their income, all of which will increase the motivation of young farmers.
Keywords: 330; agriculture; generation change; ageing farmers; generation renewal; young farmers